1994
DOI: 10.3758/bf03200867
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in mental animation during mechanical reasoning

Abstract: In three experiments we tested the effects of spatial visualization ability on performance of a motion-verification task, in which subjects were shown a diagram of a mechanical system and were asked to verify a sentence stating the motion of one of the system components. We propose that this task involves component processes of (1) sentence comprehension, (2) diagram comprehension, (3) text-diagram integration, and (4) mental animation. Subjects with low spatial ability made more errors than did subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
2
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(134 citation statements)
references
References 20 publications
5
119
2
8
Order By: Relevance
“…We did find that a large proportion of eye fixation sequences followed causal paths. The high incidence of these causal fixation sequences is perfectly compatible with the kinematic-dynamic mental model of devices that has been investigated by Hegarty (Hegarty, 1992;Hegarty & Just, 1993;Hegarty et al, 2002;Hegarty & Sims, 1994) and by . Hegarty has reported that these causal paths are prevalent in mental animations of device operations, in addition to the visual inspection of illustrated texts.…”
Section: Discussionsupporting
confidence: 59%
“…We did find that a large proportion of eye fixation sequences followed causal paths. The high incidence of these causal fixation sequences is perfectly compatible with the kinematic-dynamic mental model of devices that has been investigated by Hegarty (Hegarty, 1992;Hegarty & Just, 1993;Hegarty et al, 2002;Hegarty & Sims, 1994) and by . Hegarty has reported that these causal paths are prevalent in mental animations of device operations, in addition to the visual inspection of illustrated texts.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with other research on static displays (e.g., Hegarty & Sims, 1994), we believe that forecasters animate static displays (or parts of the displays) mentally, and use that information to create a dynamic mental representation of atmospheric dynamics, e.g., how a front would move. Or they blend different weather models to create a dynamic mental representation of the most probable path for a weather system.…”
Section: Discussionsupporting
confidence: 66%
“…is that they can impose a high working memory load when the task is to reason about a machine in motion (Hegarty & Sims, 1994;Narayanan, Suwa, & Motoda, 1994;Sims & Hegarty, 1997). However, many studies have found that animations by themselves do not improve performance (Byrne, Catrambone, & Stasko, 1999;Mayer & Anderson, 1991;Palmiter & Elkerton, 1993;Palmiter, Elkerton, & Baggett, 1991;Rieber, Boyce, & Assad, 1990) unless they provide more information than static images (Pane, Corbett, & John, 1996;Tversky, Morrison, & Betrancourt, 2002).…”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 99%
“…While the conditions of its instructional effectiveness are still unclear, the factors that influence the processing of animation have been largely identified. Three categories may be distinguished; those a) specific to the learners, such as their prior knowledge level (ChanLin, 1998;Kalyuga, 2008) and visuospatial ability (Hegarty & Sims, 1994;Lowe & Boucheix, 2009;Yang, Andre, & Greenbowe, 2003), b) specific to the instructional material, such as the type of dynamic changes within the animation (Lowe, 2003), its perceptual salience (Lowe & Boucheix, 2009;Schnotz & Lowe, 2003), the presence of accompanying information (Ginns, 2005;Moreno & Mayer, 1999;Tabbers, 2001) or the control over the pace of the animation (Fischer, Lowe, & Schwan, 2007;Mayer & Chandler, 2001), and c) specific to the learning context e e.g., the type of knowledge and the instructional domain Schneider, 2007).…”
Section: Introductionmentioning
confidence: 99%